La representación descriptiva y simbólica de las mujeres en el proceso de paridad de género en Sistemas Normativos Indígenas de Oaxaca, México - Galar Martínez, Carina (El Colegio de México A.C., 2021)
The article analyzes the descriptive and symbolic political representation of women who hold positions in the councils of municipalities with indigenous normative systems, in the state of Oaxaca, Mexico. Despite an unprecedented increase in the number of appointments (descriptive representation), these roles mostly correspond to family duties; the text considers this situation from the indigenous community perspective and in terms of possible implication in reproducing existing power relations characterized by gender inequality (symbolic representation). An analysis of 2016 and 2019 elections comparing the number of female municipal presidents and trustees appointed in the 417 municipalities, recognizing their self-determination to elect their councils, as well as the type of public offices mostly occupied by women is based on the legal an social context of the gender parity process. This data incorporates the perspectives of  the arguments put forward by some actors that allow us to explain women’s roles in the political life of Oaxaca’s indigenous communities.